Experimental and numerical study of insulation walls containing a composite layer of PU-PCM and dedicated to refrigerated vehicle. (April 2017) - Michel, Benoit; Glouannec, Patrick; Fuentes, Adrien; Chauvelon, Philippe
Highlights: A design study of an insulation wall for a refrigerated vehicle is carried out. PU-PCM composite plates with high energy storage density are characterized. Experimental and numerical studies of multilayer insulation walls are performed. Abstract: This paper presents an experimental and numerical design approach for a multi-layer insulation wall dedicated to refrigerated vehicles and containing a composite layer of PU-PCM foam. The thermal performances of the insulation walls and the thermal properties of the insulation materials are investigated using complementary experimental tools at different scales (a few mg to ≈100 g). In addition, a 1D FEM model of heat and mass transfer within the wall is implemented. Two PU-PCM composites with high energy storage capacities (i.e. high PCM mass rate) are characterized at small and large scales. Although local inhomogeneity of the distribution of PCM microbeads within the composite material is highlighted, the complementary experiments allowed measuring the average PCM mass rates of the composite materials: 35%w and 43%w. Furthermore, the study of the multilayer insulation wall shows the importance of the location of the composite layer inside it. Four multilayer wall geometries were tested to define the optimization trails. The energy crossing the inner face of the insulation wall during the "road delivery period" fell by as much as 18% for the scenario, materials and geometries studied. It was observed that the composite material must be placed close to the external wall of the vehicle.